1993
DOI: 10.1128/iai.61.2.464-469.1993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polysaccharide capsule and methods of preparation on human lymphocyte proliferation in response to Cryptococcus neoformans

Abstract: Ciyptococcus neoformans is a pathogenic encapsulated yeast that infects patients that have defective cell-mediated immunity, including AIDS patients. Whole cryptococcal organisms that are killed by heating stimulate normal human lymphocytes to proliferate. However, strains of C. neoformans vary widely in virulence and therefore in their ability to cause disease in humans. To determine the effect of virulence factors such as the cryptococcal capsule, serotype, and the state of the organisms on the lymphocyte re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 35 publications
7
29
0
Order By: Relevance
“…To our knowledge, this is the first demonstration in which GXM inoculation alters cytokine production by splenocytes from an immunocompetent host, and these data confirm previous observations from experiments performed in vitro by our laboratory and others. 13,[15][16][17][18] In addition, we have previously published IL-10 involvement in the immunosuppressive phenomenon that occurred 14 days after intraperitoneal C. neoformans infection in rats. 17 The cellular population and mechanisms involved in the in vivo modification of cytokine profile by GXM remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first demonstration in which GXM inoculation alters cytokine production by splenocytes from an immunocompetent host, and these data confirm previous observations from experiments performed in vitro by our laboratory and others. 13,[15][16][17][18] In addition, we have previously published IL-10 involvement in the immunosuppressive phenomenon that occurred 14 days after intraperitoneal C. neoformans infection in rats. 17 The cellular population and mechanisms involved in the in vivo modification of cytokine profile by GXM remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In this sense, several studies have indicated that this high-molecular-weight polysaccharide could be responsible for the pathobiological phenomena attributed to the capsule. [12][13][14][15][16] Experiments performed in vitro with human or murine mononuclear cells have shown that C. neoformans capsular polysaccharides impair lymphoproliferation, [12][13][14] induce interleukin (IL)-4 and IL-10 by splenic adherent cells from mice 15 and GXM, in particular, stimulates IL-10 liberation by human monocytes. 16 In accordance with these findings, we have also demonstrated in our laboratory the ability of purified GXM to induce non-specific suppression of T lymphocyte activation and Th2 cytokine profile in cultures of spleen mononuclear (Spm) cells from normal rats.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of purified GXM to influence IL-12Rb2 expression is consistent with the known inability of GXM to activate T cells directly. 6 In contrast, acapsular cryptococci proved to be potent stimulators of IL-12Rb2 expression. The addition of GXM and acapsular cryptococci also produced appreciable stimulation of IL-12Rb2 expression, however, the number of positive cells was considerably lower than that found after stimulation with acapsular cryptococci alone.…”
Section: Resultsmentioning
confidence: 98%
“…Firstly, soluble GXM can directly influence cells responding to the yeast. 6,10 Secondly, GXM, inhibits the phagocytosis of yeast cells when organized into a capsule. 25 GXM alone had no effect on T-cell IL-12Rb2 expression showing that this compound is not per se a negative signal on the cytokine receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…Glucuronoxylomannan (GXM) is the major constituent of the capsular material and is believed to contribute to virulence by interfering with effective immunological responses (Vecchiarelli, 2000). There is evidence that GXM suppresses both humoral and cellular responses (Murphy and Cozad, 1972;Mody and Syme, 1993), and extensive studies have investigated its antigenic characteristics in the elicitation of humoral immune factors (Vecchiarelli and Casadevall, 1998).…”
Section: Introductionmentioning
confidence: 99%